RELASI AGAMA DAN SOSIAL MASYARAKAT SEBAGAI FENOMENA RELIGIUS - Miftahusyai'an, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Historically, all religions born, grew, and developed from the area of Eastern civilization (or rather Asian). There are two central points of eastern civilization that caused those religions, namely: 1) Middle East (and South Asia) in this area was appeared some religions: Judaism, Christianity, Islam, Hinduism and Buddhism, and 2) East Asia was appeared some religions: Tao (ism), Confucianism (Konfusianism), and Shinto. From these central points was born and grew religion to be a part of the history of mankind. The real society is a religious phenomenon. This religiousness is revealed from the fact that people are always trying to worship extraordinary things such as: nature (sun, sea, fire, mountain, etc.), charismatic spiritual leaders, technology or Individual â€Supra-Inderawi